"Nata De Vable" Minuman Kaya Serat, Banyak Manfaat, dan Harga Bersahabat - Wafa, Anastasia Ahmad Zuhri; Wibisono, Sofian Arissaputra; Baskoro, Adhimas Setyo; Rizeki, Ahmad (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Children are given the most beautiful gift of god. Parents should always monitor the progress and growth of the child, one about nutrition in children. If nutrition is metthen the child grow healthy. One of the most important nutrition is the consumption of vegetables. In todays kids do not like vegetables, they prefer foods that practical. Though eating vegetables is necessary forthe body. Vegetables are very banyan kinds, one of which is spinach. Spinach is very good for health, especially for children. To anticipate that children prefer to vegetables, we should cultivate the vegetables into a new food innovation nutritional content still awake. One innovation is the nata with spinach raw material. It is expected that with the new process of children can be met nutritional and will cultivate vegetable consumption. In addition as an alternative food for children, processed nata from spinach also has a high economic value that can be developed into a profitable business in the future.Keywords : children, spinach, nata, higheconomic value